Reformulation of the Investigative Mechanism for Medical Personnel in Alleged Malpractice Resulting in Patient Death Based on the Due Process of Law Principle in the New 2026 Criminal Procedure Code - Arthur Daniel Thomas Betlehem; Azis Budianto (Journal Customary Law, 2026)
This study aims to analyze and reconstruct the legal standing of professional organization recommendations in the investigation of medical personnel suspected of causing patient death from the perspective of reforming Indonesian criminal procedure law. The research problem arises from the disharmony of norms between the investigator's authority in criminal procedure law and the provisions of Law Number 17 of 2023 concerning Health, specifically Article 308 which requires a recommendation from the Professional Disciplinary Council before legal proceedings against medical personnel are carried out. In practice, this provision is often interpreted as an absolute requirement (de facto) that has the potential to limit the investigator's authority as regulated in criminal procedure law and create legal uncertainty. This study uses a normative juridical method with a statutory and conceptual approach. The results show that normatively, professional organization recommendations do not have binding force as a requirement for initiating an investigation, but rather only serve as a form of persuasive expert testimony. However, the formulation of norms in Article 308 of the Health Law which uses the phrase "a recommendation must first be requested" creates normative ambiguity and a conflict of authority between law enforcement officials and professional organizations. Therefore, this study proposes a legal reconstruction through a mandatory consultative model with a double-gate mechanism approach, namely an ethical/disciplinary screening mechanism that runs parallel to criminal investigations without eliminating the investigator's authority. This reconstruction is expected to harmonize criminal procedure law and health law and ensure a balance between the protection of medical personnel, patient rights, and legal certainty in the Indonesian criminal justice system.